Conversor buck-boost interleaved com modulação em frequência aplicado a correção de fator de potência - Zytkowski, Vitor Alexandre (2023)
This work proposes a new switching cell applied at a AC-CC buck-boost converter with switching frequency modulation (SFM) used as a power factor corrector (PFC), Soft-switching and no reverse recovery time problems are achieved with SFM. This converter presents, due to the SFM, the characteristics of a voltage follower with a distortion proportional to the output voltage, this gives the converter the advantage of not needing a current loop. This thesis presents the operating principle, a mathematical analysis of the converter and the practical results of a 1 kW buck-boost in continuous conduction mode (CCM), together with a normative analysis of its harmonic distortion according to the IEC 61000-3-2.